(3eYGOdI GdSYGOIs - (3bUhOI, YHO Gddgs ((3GdbGgQIs (3cJGHj ddfTQ hGdJhRjYs, 2015)
(3gPG GdcJGH jQcR Ydi Cf jLYdc JfLM aj MjGJc HWQb YdejI heHSWI aj WQjbI WQMgG hTQMgG(B.. (3WQb hGSJQGJjLjGJ hHMhK bO Je JMUjdgG hLeYgG hJfbjMgG dJUHM eKGHQG heMHG ddYed hGdEfJGL, hJVY CgOGaG dfaSc hJbhe HJMbjbgG hJZjQ bfGYGJc GdSdHjI Yf faSc hMjGJcs
4 11
Keywords: (3GdJaGDds; (3GdSQhQs; (3GdSYGOIs; (3GdaQMs